CREATION OF 3D OBJECTS IN APPLIED AND DIGITAL ART USING MODERN TECHNOLOGIES (American Journal of Technology and Applied Sciences, 2025)
This article is devoted to the analysis of modern technologies used in the creation of objects of applied and digital art. The discussion includes tools and methodologies such as virtual and augmented reality, artificial intelligence, generative algorithms, and digital media. Special attention is given to the integration of these technologies into applied art and to the transformation of visual art into interactive digital forms. The article analyzes challenges related to authorship, sustainability, educational requirements, and the aesthetic considerations of digital creativity.